Pencegahan Perilaku Menyimpang Remaja Melalui Seminar Parenting Pendekatan Emosi Anak oleh Orangtua bagi Wali Murid MTs Mazro’atussibyan Cengal Karacak - Nuraini; Mutawarudin (Indra Institute Research & Publication, 2024)
This community service activity is focused on parents/guardians of students at the junior high school level, namely those parents who have children in their teens. Because at this age, students/children are vulnerable to committing deviant behavior because at this age individuals are in the age of conflict/search for identity. The first thing discussed in this service activity is the growth and development of teenagers, developmental tasks in adolescence and the conflicting behavior of teenagers at this age who tend to have high curiosity so that they need to be given an effective approach and communication between parents and children/ these teenagers so that they do not fall into deviant behavior. This PkM activity is carried out by means of a direct seminar to parents regarding emotional approaches to children by parents in order to prevent deviant behavior in teenagers. As a result of the implementation of this seminar activity, students/parents have an understanding of teenagers, the challenges of parenting in adolescence as well as an emotional approach to preventing deviant behavior in teenagers. With this understanding, it is hoped that they will be able to implement effective parenting patterns, namely being able to establish good emotional closeness and communicate effectively with their teenagers so that their teenagers will feel comfortable in the family environment so that the teenagers will not look for their identity outside in the wrong way or behave in deviant ways.